2018
DOI: 10.7554/elife.31037
|View full text |Cite
|
Sign up to set email alerts
|

YAP and TAZ regulate adherens junction dynamics and endothelial cell distribution during vascular development

Abstract: Formation of blood vessel networks by sprouting angiogenesis is critical for tissue growth, homeostasis and regeneration. How endothelial cells arise in adequate numbers and arrange suitably to shape functional vascular networks is poorly understood. Here we show that YAP/TAZ promote stretch-induced proliferation and rearrangements of endothelial cells whilst preventing bleeding in developing vessels. Mechanistically, YAP/TAZ increase the turnover of VE-Cadherin and the formation of junction associated interme… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

15
209
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 204 publications
(229 citation statements)
references
References 58 publications
15
209
0
Order By: Relevance
“…Highly distended lacteals reacted with a limited proliferative response (Appendix Fig S5), which may have been caused by increased mechanical stretch due to obstruction of the mesenteric collectors. Such mechano‐stimulation of LEC proliferation has been shown to be VEGFR‐3‐mediated and independent of VEGF‐C levels, but dependent on YAP/TAZ nuclear localization (Planas‐Paz et al , ; Neto et al , ). Supporting the assumption that intestinal defects were caused by the demise of mesenteric collectors, mesenteric defects temporally preceded fragmentation of lacteals (Figs EV3 and EV4).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Highly distended lacteals reacted with a limited proliferative response (Appendix Fig S5), which may have been caused by increased mechanical stretch due to obstruction of the mesenteric collectors. Such mechano‐stimulation of LEC proliferation has been shown to be VEGFR‐3‐mediated and independent of VEGF‐C levels, but dependent on YAP/TAZ nuclear localization (Planas‐Paz et al , ; Neto et al , ). Supporting the assumption that intestinal defects were caused by the demise of mesenteric collectors, mesenteric defects temporally preceded fragmentation of lacteals (Figs EV3 and EV4).…”
Section: Discussionmentioning
confidence: 99%
“…Mesenteric LECs that had lost VEGFR‐3 surface expression, but upregulated VEGFR‐2, which has previously been reported for retinal blood vessels (Zarkada et al , ). Proliferation of ECs in response to VEGF‐A is independent of YAP/TAZ (Neto et al , ). Still YAP/TAZ can become activated downstream of VEGF‐A or in response to mechanic signals and then provide the optimal transcriptional program for VEGF‐driven endothelial proliferation (Wang et al , ; Neto et al , ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cytoplasmic localization of YAP is primarily governed by its phosphorylation; thus, dephosphorylated YAP translocates into the nucleus, where it binds transcriptional factors, triggering the expression of target genes while limiting its own cytoplasmic sequestration and subsequent degradation (Zhao et al, 2007). An increasing number of studies have shown that VEGF induces YAP activation via promoting its nuclear translocation and the activity of YAP is required for transducing the VEGF signal into a specific transcriptional program, needed for a full angiogenesis response (Neto et al, 2018). Deletion of YAP is responsible for the impaired cytoskeleton rearrangements and VEGFR2 trafficking to the membrane in ECs, leading to compromised angiogenesis (Wang et al, 2017).…”
mentioning
confidence: 99%
“…Fluorescence immunostaining with isolectin B4 (IB4) and anti-GFAP showed accordant localization of endothelium and astrocytes, respectively, from P3 to P21 ( Figure S1A,B). YAP, a transcriptional coactivator in Hippo signalling, is an important regulator of angiogenesis, 11 as well as retinal vascular development. However, the effect of YAP on the relationship between astrocyte growth and blood vessels needs to be elucidated.…”
Section: Yap Is Critical For Retinal Vessel Developmentmentioning
confidence: 99%